Treatment of underlying language impairment to overcome perseveration: A case study - S.P. Goswami and Rachel C. Francis (Journal of All India Institute of Speech and Hearing, 1970)
Perseveration has always been a challenge for Speech-Language Pathologists working with patients with adult language disorders. With the recent theoriesand approaches towards treating perseveration, treating the underlying language processing diculty (Moses, Sheard & Nickels, 2004) has shown someevidence to help persons with aphasia (PWA) overcome verbal perseveration. Therefore, the task lies in understanding PWA language processing abilitiesand where the block in the processing is occurring. Based on this theoretical background, this paper presents a case of Broca's Aphasia with severe perseveration.